(untitled) (Culturas Científicas, 2022)
Although examples coming from biochemistry have already been explored in the philosophy of sciences as case studies, the philosophy of biochemistry (i.e. the systematic philosophical study of the metascientific problems of this science) is a nascent subdiscipline. In this article, two philosophical problems of contemporary relevance within this science will be explored. First, we are going to examine the epistemological bases of the protein folding problem, mostly concerning protein 3D structure prediction from its sequence, which has given much to talk about due to new advances involving deep learning. Second, we will explore the in-vitro/in-vivo problem and, more generally, the extrapolation problem in biological sciences. Finally, taking into account the consequences of both subjects, we will consider some philosophical reflections about reductionism, pluralism and the place of biochemistry among biological sciences.